Effect of a Combination of Extract of Centella asiatica L. Leaves and Extract of Green Coffee (Coffea canephora robusta P.) Beans in a Cream Preparation for Grade 1-3 Cellulite and Slimming - Primastuti, Riska Febriadne; Wih, Wong Lip; Mun’im, Abdul (Makara Journal of Science, 2013)
An accumulation of fat in the subcutaneous tissue causes cellulite and dimpling on the surface of the skin. Although not related to obesity, obesity worsens cellulite. There are abundant topical anticellulite creams on the market, but the efficacy of these creams has not been scientifically proven. A combination of Centella asiatica L. leaves extract and green coffee (Coffea canephora robusta P.) bean extract in a cream preparation was clinically tested in 30 women for 84 days in the absence of diet and exercise. The descriptive-true experimental before (T-0)-after (T-84) method was used to classify the cellulite (grade 1–3) and to determine the slimming effect. The cellulite appearance and the body circumferences (abdominal and thigh) perimeters were photographed 5cm and 10cm below the navel and below the gluteal fold. The results of before and after the treatment showed that grade 1 cellulite lower (p < 0.000), the measurement of abdominal circumference showed reduction (p < 0.013), but the measurement of both thigh circumference showed insignificantly reduction (p < 0.512). The combination of both extracts reduce cellulite and fat deposits in the abdominal area, making the volunteers look slimmer